Do pecado à redenção: o papel das primeiras damas e a infância marginal em Cascavel-PR - Santos, Lucas Cardoso dos (2012)
This paper has the objective to stablish a critical reflection on the political participation of first laddies in Cascavel-PR between 1990 and 2007, particularly considering their relation to public social assistance. As Brazil is a country colonized by europeans, the Christian tradition was quite influent in the colony development and for that it was part of feminine world to deal with a dark destine in which it was believed that the women were addicted to the desires of the flesh, in other words, to the sin, and this made them an object of care and constant observation by those who belonged to other social groups. That resulted on women’s imprisonment in the interior of private spaces and consequently in their social banishment. The starting point of this analysis was to look for the understanding of factors that made possible and, later on, legitimate the feminine submission to the male genre. After that, the processes that allowed the women’s insertion in social life and mainly the transformations in the social environment by their entrance in the political life articulated to the new requirements of the economic system was analyzed. The study was based on the hypothesis that the centuries of exclusion that kept women basically at home also resulted into their distance from the political matters. This way, being the politics an area of dispute and interests, it wouldn’t be compatible with the feminine ideal of innocence and purity. It was then established one of the first problematics proposed in this study, being man or woman in the Ocident becomes something much bigger than the simple physiologic difference; it involves absorbing the personal actions of each one defined socially. It was noticed that even the feminine political participation turned to social assistence was only possible due to the qualities that are considered basically feminine as abnegation, solidarity, care and others. Having mentioned that, it was analyzed the experience lived by first ladies in Cascavel-PR whose participation in the social area has been understood as support to poor people. In special, the attention was centered on the marginal childhood history of the city, once the social area is quite broad and many ones depend on it. Besides that, in the 90s Cascavel was going through a difficult time involving youngsters that exposed themselves to the street risks and entered in the drug world.